Fluorescent cross-linked polystyrene perylenebisimide/oligo(p-phenylenevinylene) microbeads with controlled particle size, tunable colors, and high solid state emission - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2013)
A series fo cross-linked fluorescent polystyrene (PS) microbeads with narrow size distribution and intense solid state emission was developed. Fluorophores based on perylene bisimide (PBI) and oligo(p-phenylenevinylene) (OPV) designed as acrylic cross-linkers were introduced into the polymerization recipe in a twostage dispersion polymerization, carried out in ethanol in the presence of poly(vinylpyrrolidone) (PVP) as stabilizer. The structural design permitted introduction of up to 10(-5) moles of the fluorophores into the polymerization medium without fouling of the dispersion. The particle size measured using dynamic light scattering (DLS) indicated that they were nearly monodisperse with size in the range 2-3 mu m depending on the amount of fluorophore incorporated. Fluorescence microscope images of ethanol dispersion of the sample exhibited intense orange red emission for PS-PBI-X series and green emission for PS-OPV-X series. A PS incorporated with both OPVX and PBIX exhibited dual emission upon exciting at the OPV wavelength of 350 nm and PBI wavelength of 490 nm, respectively. The low incorporation of fluorophore resulted in almost complete absence of aggregation induced reduction in fluorescence as well as red-shifted aggregate emission. The solid state emission quantum yield measured using integrating-sphere setup indicated a very high quantum yield of phi(powder) = 0.71 for PSOPV-X and phi(powder) = 0.25 for PS-PBI-X series. The cross-linked PS microbeads incorporating both OPV and PBI chromophores had a phi(powder) = 0.33 for PBI emission and phi(powder) = 0.20 for OPV emission. This strategy of introducing fluorophore as crosslinkers into the PS backbone is very versatile and amenable to simultaneous addition of different suitably designed fluorophores emitting at different wavelengths.
Keywords: dispersion polymerization; dual emission; fluorescent cross-linker; oligo(p-phenylenevinylene); Perylenebisimide; solid state fluorescence

Fluorescent polystyrene microbeads as invisible security ink and optical vapor sensor for 4-nitrotoluene - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2016)
Color-tunable solid-state emitting polystyrene (PS) microbeads were developed by dispersion polymerization, which showed excellent fluorescent security ink characteristics along with sensitive detection of vapors of nitro aromatics like 4 nitro toluene (4-NT). The fluorophores pyrene and perylenebisimide were incorporated into the PS backbone as acrylate monomer and acrylate cross-linker, respectively. Solid state quantum yields of 94 and 20% were observed for the pyrene and perylenebisimide, respectively, in the PS/Py and PS/PBI polymers. The morphology and solid state fluorescence was measured by SEM, fluorescence microscopy, and absorbance and fluorescence spectroscopy techniques. The ethanol dispersion of the polymer could be used directly as a fluorescent security ``invisible'' ink, which became visible only under ultraviolet light. The color of the ink could be tuned depending on the amounts of the pyrene and perylenebisimide incorporated with blue and orange-green for pyrene alone or perylenebisimide alone beads respectively and various shades in between including pure white for beads incorporating both the fluorophores. More than 80% quenching of pyrene emission was observed upon exposure of the polymer in the form of powder or as spin-coated films to the vapors of 4-NT while the emission of perylenebisimide was unaffected. The limit of detection was estimated at 10(-5) moles (2.7 ppm) of 4-NT vapors. The ease of synthesis of the material along with its invisible ink characteristics and nitro aromatic vapor detection opens up new opportunities for exploring the application of these PS-based materials as optical sensors and fluorescent ink for security purposes.
Keywords: dispersion polymerization; invisible security ink; Perylenebisimide; pyrene; solid state detection